PERAN LEMBAGA KEUANGAN MIKRO TERHADAP PENGUATAN USAHATANI BAWANG DAUN DI KECAMATAN SUKAPURA KABUPATEN PROBOLINGGO - Ana Arifatus Sa’diyah; Dyanasari Dyanasari (Universitas Tribhuwana Tunggadewi, 2014)
After the eruption of Mount Bromo led to a decline in the area planted vegetables decrease thein come of the people in the area. The intervention of Micro finance Institutions (MFIs) as a financial intermediary which aims to provide easier access to credit for low-income farmers vegetable or vegetable growers after the eruption of Mount Bromo that do not have access to commercial banks, is expected to increase farm production scallion, after Bromo Mountain eruption there are. The aims of this research are to investigate the conception of potatoes farm (cost, supply, benefits and R/C) factors that influence the vegetables farm productivity in Sukapura, and the role of micro finance on farm. The research was conducted in Ngadisari and Ngadirejo with purposive sampling method. Data which is obtained from the research is analyzed using R/C and Cobb-Douglass function. The results show that anion farm is beneficial with R/C value >1, the vegetables production are influenced by seeds, land area, biofertilizer, labor, perticides and micro finance have significant role on helping the farm